Curriculum integration in teacher training: a reflection focused on supervised teaching practice at the higher school of education of Viseu - Cardoso, Ana Paula (2013)
The Master's degree in Pre-School Education and Teaching in the 1st Cycle of Basic Education, in accordance with the present legislation, includes the component of Supervised Teaching Practice (STP). The way to organize this training component, although regulated by some principles contained in the legal documents, is of the responsibility of each institution of higher education that teaches the course. In this communication, we present a study that aims to reflect on the model of organization and functioning of the STP implemented in the Higher School of Education of Viseu (Portugal).